Online digital archive of aerial photographs (1935–1941) of Ethiopia. (18th March 2021) - Nyssen, Jan; Debever, Martijn; Gebremeskel, Gezahegne; De Wit, Bart; Hadgu, Kiros Meles; De Vriese, Steven; Verbeurgt, Jeffrey; Frankl, Amaury; Besha, Tulu; Kropáček, Jan; Forceville, Astrid; Demissie, Biadgilgn
Abstract: The archive of aerial photographs, dating 1935–1941 and covering parts of north and central of Ethiopia, is one of the few archives with pre‐1960 remotely sensed data in Africa. It allows adding 30 years of time depth for geographical studies, in contrast to the commonly known oldest imagery dating to 1964, sometimes 1958. These photographs were originally acquired by the Italian military forces, to obtain raw material for warfare purposes and the production of topographic maps. To make the archive accessible, it has been scanned and georeferenced. Procedures used in georeferencing and digitally archiving are detailed in this paper, as well as our experiences with orthorectification and use of the photosets in scientific research. This data set of aerial photographs of Ethiopia in the 1930s has been availed to the wider scientific community through the Pangaea website http://doi.org/10.1594/PANGAEA.920077 (Nyssen et al ., 2020, Aerial photographs of Ethiopia 1935–1941 ) Additionally, a web interface (http://www.ethiopia1935.ugent.be/ ) allows scientists visualizing the location of relocated photographs, and to select and freely order scenes of interest. Abstract : The archive of aerial photographs (right), dating 1935–1941 and covering parts of north and central of Ethiopia, was originally acquired by Italian military forces. To make the archive accessible, it has been scanned and georeferenced (left). This data set of aerial photographs of Ethiopia in the 1930s has been availed to the wider scientific community through the Pangaea website. Additionally, a web interface allows visualising the location of relocated photographs, and to select and freely order scenes of interest.